Efficacy and tolerability of the histone deacetylase inhibitor panobinostat in clinical practice. Issue 1 (7th July 2017) - Baertsch, Marc‐Andrea; Hillengass, Jens; Blocka, Joanna; Schönland, Stefan; Hegenbart, Ute; Goldschmidt, Hartmut; Raab, Marc S.
Abstract: The histone deacetylase inhibitor panobinostat has shown efficacy in phase‐II and phase‐III trials for multiple myeloma and has recently received market approval in combination with bortezomib and dexamethasone. Here, we retrospectively report our single center experience with panobinostat/bortezomib/dexamethasone (FVD) in a heavily pretreated patient population (n = 24) with a high degree of refractoriness to proteasome inhibitors (PI) and immunomodulatory drugs (IMiD). Median age was 67 years (range 49‐87) and the median number of prior therapies was 5 (range 2‐17). Fourteen patients (58%) had high‐risk cytogenetic aberrations. Thirteen (54%) and 21 (88%) patients were refractory to PIs and IMiDs, respectively. Twelve patients (50%) were refractory to bortezomib and 7 (29%) to carfilzomib; 6 patients (25%) were refractory to both bortezomib and carfilzomib. In 21 patients evaluable for response, overall response rate (ORR; ≥PR) was 33% (7/21) and 81% (17/21) achieved at least stable disease. Median progression‐free survival (PFS) and overall survival were 3.5 and 9.8 months, respectively. Significant differences between bortezomib‐sensitive and ‐refractory patients were observed. In bortezomib‐sensitive patients, median PFS was 6.3 months compared to 2.3 months in bortezomib‐refractory patients ( P < .001). Median overall survival was not reached vs 4.8 months ( P = .046) in bortezomib‐sensitive and bortezomib‐refractory patients, respectively. The only patient refractory to carfilzomib but sensitive to bortezomib achieved very good partial remission and PFS of 6.3 months, suggesting discrete mechanisms of resistance to different PIs. As expected, thrombocytopenia and fatigue/asthenia occurred in nearly all patients (96% and 83%, respectively). Diarrhea was observed in only 19% of patients which compares favorably with the high rates of diarrhea reported in the PANORAMA trials. With panobinostat dose reductions in 67% of patients, FVD was tolerated by the majority of patients. In conclusion, FVD showed efficacy in a heavily pretreated, high‐risk multiple myeloma population with a high degree of patients refractory to novel agents including PIs.